Biomass and bioenergy perspectives of a coal region: status quo, potential and scenarios in Lusatia - Leuner, Bruna; Hirschl, Bernd (Frontiers in Energy Research, 2024)
Coal has been one of the main fuels used in Europe. Its decreasing role due to the ongoing transformation of the energy system will create significant socio-economic challenges. The switch into renewable energy systems could be an alternative to maintain jobs and economic activities within the affected regions. Biomass use and bioenergy can play an important role in the energy transition. Instead of energy crops, forest and agricultural residues should be used as biogenic energy sources in the future to avoid impacts on land use and food security. The main objective of this article is to investigate the biomass potential of a coal region and to provide scenarios for the future development of bioenergy production. Due to the changing framework conditions and, as a result, the different biomass focuses, previous bioenergy potential estimates must be reviewed. The methods for determining the potential of biomass for energy production was used for Lusatia, the second largest coal region in Germany. These methods can also be applied in other regions. As a first step, the regional status quo assessment of cultivated areas and yields had decisive relevance for calculating biomass potential ranges. In a second step, the current bioenergy facilities in the region were identified, with a focus on power and heat production. The third step was the estimation of future regional bioenergy use. Therefore, the regional potential was gathered with the generally supra-regional framework conditions. For this purpose, national scenario studies were used, which contain the relevant target values and framework conditions. Two scenarios were developed for future bioenergy estimations: a conservative path based on the current policies and a progressive path, derived from the goal of climate neutrality by 2045. The results show a qualitative comparison among both scenarios and the previously determined potential ranges. Bioenergy can contribute to achieving climate neutrality with an increase in wood-fired systems, while agricultural bioenergy potential is likely to decline. In the discussion, however, the uncertainty of these results is pointed out, as future use of bioenergy will be heavily influenced by the regulatory framework, competition with material use and the influences of climate change.